SISTEM INFORMASI SUMBER DAYA MANUSIA PADA KANTOR DESA SUKA MAJU MENGGUNAKAN ENKRIPSI AES - Mega Mustika; Febri Dristyan; Rezagi Meilano (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2026)
Human resource management at the Suka Maju Village Office is not yet integrated, leading to potential delays and data inaccuracies. This study aims to design a web-based Human Resource Information System by implementing Advanced Encryption Standard (AES) to secure sensitive employee data. The system is developed using the Rapid Application Development (RAD) method and user feedback–based prototyping, covering integrated management of employee data, attendance, leave, payroll, and reporting. The results indicate that the system improves the efficiency of human resource management and enhances employee data security.